Role of reliable person in soviet system - Okuličiūtė , Lina (Genocidas ir rezistencija, 2006)
During the Soviet regime in Lithuania, the agency network – the undercover aides of the Soviet security – formed the pillar of the KGB agency. When the agency network was reorganised in 1952, the category of informant was replaced by a new category of trusted persons. The difference between the agency and the trusted persons was that the latter were used to deal with a wide range of issues and investigate objects, while the agency was established for counterintelligence tasks. They were to be a KGB source for gauging people’s moods, topics of discussions, attitudes towards Soviet policies and other tasks.
Keywords: KGB; agents; reliable person; antisoviet resistance; collaborators